A forest on the edge: Causes of synchronous Early Holocene forest declines in northern Greece and the implications for the introduction of farming to Europe - Lieveke van Vugt; Erika Gobet; Jacqueline F.N. van Leeuwen; Kathrin Ganz; Tryfon Giagkoulis; Sönke Szidat; Hendrik Vogel; César Morales-Molino; Amy Bogaard; Kostas Kotsakis; Albert Hafner; Willy Tinner (Quaternary Environments and Humans)
We present a high-resolution continuous palaeoecological study covering the transition from foraging to farming at Limni Vegoritis, a large lake in western Macedonia, Greece. We show how the pristine mixed deciduous oak woodlands from the Early Holocene were severely affected by a climate anomaly in the Eastern Mediterranean between 8600 and 7800 cal yr BP (6650–5850 cal BCE). A strong reduction in moisture availability pushed the deciduous oak woodlands across a tipping point, significantly reducing their abundance. As the woodlands declined, the vegetation became more open, and drought-adapted steppe vegetation and juniper brushlands expanded around the lake. The marked forest disruption at ca. 8600 cal yr BP (6650 cal BCE) provided favourable conditions for the introduction of Neolithic farming to mainland Greece and Europe, as suggested by pollen and spores indicative of arable and pastoral farming. We hypothesise that the temporary climate-driven development of steppe-like grasslands and shrublands advantaged the introduction of drought-adapted crops (e.g. cereals) and domesticated animals from regions in southwest Asia with similar vegetation and climate conditions. After 7800 cal yr BP (5850 cal BCE) when the climate impact on the vegetation declined, pine forests spread, followed by increases of trees like Ostrya and Fagus from ca. 7000 cal yr BP (5050 cal BCE). The combination of climate change with Neolithic land use likely continued to affect vegetation and facilitated such changes in forest composition, promoting more oceanic and/or disturbance-adapted species.